Local Business Empowerment through Herbal Innovation and High Value Powder Products in Sugeng Village - Cantika Yulianing Tyas; Rizky Eka Febriansah; Farika Rizqi Amalia; Sevya Dwi Gita Nurani; Wardha Hani Aulia; Septiarni Mar'atus Sholichah; Mukhammad Ariya Alamsha (Indonesian Journal of Cultural and Community Development, 2024)
This service aims to increase the production of herbal plants in Sugeng Village through the implementation of sustainable and environmentally friendly agricultural practices. By using research methodology to allocate training for farmers and local entrepreneurs related to organic farming practices, herbal product processing, and business management, involving specialists in the manufacture of creative and attractive herbal powder products and packaging designs that increase product attractiveness. The results of this service are herbal powder products that have high added value in terms of quality, safety, and packaging, as well as an increase in the income of the Sugeng Village community as a result of increasing the added value of herbal products and strengthening local businesses. This service, which encourages local businesses through herbal innovation, has the potential to improve the economy of Sugeng Village and increase community income, which has a positive impact on their welfare and living standards. Highlight: Sustainable Agricultural Practices: Implementing eco-friendly methods ensures long-term viability, safeguarding the environment while boosting production. Holistic Training Approach: Equipping farmers with diverse skills in organic farming, product processing, and business management fosters self-sufficiency and entrepreneurship. Economic Empowerment: Elevating product value and local businesses not only enhances income but also enhances community welfare and living standards, fostering a thriving local economy. Keyword: Herbal Innovation, Sustainable Agriculture, Community Empowerment, Organic Farming, Economic Development